Vanuatu : Assessment of the Supervision and Regulation of the Financial Sector Volume II--Detailed Assessment of Observance of Standard and Codes. (IMF Staff Country Reports; Country Report ;, 2003)
This paper summarizes the Detailed Assessment of Observance of Standards and Codes in the financial sector of Vanuatu in the context of the offshore financial center program. It assesses the supervision and regulation of the financial sector compliance with the Basel Core Principles for Effective Banking Supervision and the International Association of Insurance Supervisors Core Principles using the Core Principles Methodology. It also assesses the elements of legal and institutional antimoney laundering and of combating the financing of terrorism.